Hand foot and mouth disease and its spatial relationship with vaccine refusal cases in Terengganu - Said, Mohamad Zarudin Mat (2018)
Background: Hand, foot, and mouth disease (HFMD) is a common viral illness that is considered as a global public health problem with pandemic potential. The progressive increment of HFMD cases in Malaysia needs further investigation especially in the tracking of the disease spread and its spatial pattern to other factor such in vaccine refusal event. Objective: This study aimed to estimate the prevalence of HFMD in Terengganu, map the geographical distribution of HFMD and vaccine refusal cases; and estimate the spatial relationship between HFMD and vaccine refusal cases. Methodology: This study applied cross-sectional design and used secondary data from the online notification system and registry maintained by the CDC and MCH Unit Terengganu State Health Department. HFMD cases and vaccine refusal cases were provided in MS Excel format and population demographic data in the ESRI shapefile format. Data were analyzed using QGIS 2.16.3 software. The number of cases per area was estimated using points-in-polygons function while the spatial relationship between HFMD and vaccine refusal cases was tested using cross-K function test. Result: There was a total of 811 notified HFMD cases in 2016 with the overall prevalence at 79.9 cases per 100,000 population. The HFMD was highly concentrated over the Kuala Terengganu, Marang and Dungun. The prevalence of HFMD ranged from 20.4 to 218.1 cases per 100,000 population. There was evidence of spatial cluster of HFMD based on the Nearest Neighbor Index, (r = 0.27, p < 0.01). Meanwhile, the locations of HFMD was statistically and closely related to the vaccine refusal cases (cross-K test, p < 0.01). Conclusion: HFMD and vaccine refusal cases formed clusters in Terengganu especially involving the high density population such as Kuala Terengganu, Marang and Dungun. Moreover both HFMD and vaccine refusal cases were closely located.